Kedudukan Pengadilan Tata Usaha Negara Dalam Penyalahgunaan Wewenang Pada Kegiatan Pengadaan Barang Dan Jasa Pemerintah - Muhamad Agev Dzulfikar (Jurist-Diction, 2022)
AbstractThe system formation and implementation of the procurement of goods and services must be carried out by applying the general principles of good governance. However, in practice, there are still various real obstacles to implementing good governance in the form of widespread authority exercised by certain parties. In addition, it is possible to examine the authorized handling mechanism carried out by Government Officials, in particular which judicial goods and services procurement officials are entitled to adjudicate. Therefore, this paper aims to discuss the competent authority for the procurement of goods and services based on administrative law as well as conflicts regarding the competence of the court in the authority to procure government goods and services. This paper is a normative legal research that puts emphasis on the legal approach. Based on administrative law, procurement of goods and the arrangement of legal relations between providers and users in the preparation process until the process of issuing a letter of determination of the provider of goods and services. Keywords: Procurement of Goods and Services; Abuse of Authority; State Administrative Court. AbstrakDalam pembentukan sistem dan implementasi dari pengadaan barang dan jasa harus dilakukan dengan menerapkan asas-asas umum pemerintahan yang baik. Namun, pada prakteknya, masih terdapat berbagai hambatan ketika menerapkan asas-asas umum pemerintahan yang baik berupa maraknya penyalahgunaan wewenang yang dilakukan oleh pihak-pihak tertentu. Selain itu, terdapat ketidakpastian mengenai mekanisme penanganan penyalahgunaan wewenang yang dilakukan oleh pejabat pengadaan barang dan jasa berupa kompetensi peradilan mana yang berhak untuk memeriksa dan mengadili. Oleh karenanya tulisan ini bertujuan untuk membahas penyalahgunaan wewenang pengadaan barang dan jasa berdasarkan hukum administrasi serta konflik aturan mengenai kompetensi pengadilan dalam penyalahgunaan wewenang pengadaan barang dan jasa pemerintah. Tulisan ini merupakan penelitian hukum normatif yang menekankan pada pendekatan hukum. Berdasarkan hukum administrasi, pengadaan barang dan jasa mengatur hubungan hukum antara penyedia dan pengguna pada proses persiapan sampai pada proses penerbitan surat penetapan penyedia barang dan jasa. Kata Kunci: Pengadaan Barang dan Jasa; Penyalahgunaan Wewenang; Pengadilan Tata Usaha Negara.